Pengaruh Perlakuan Asap Cair Tempurung Kelapa dan Larutan Kunyit Terhadap Kekuatan Impak Komposit Serat Serai Wangi (Cymbopogon Nardus) Matriks Polyester - Rienera, Salsabilla; Ary Wahyudie, Ilham; Rollastin, Boy (Jurnal Inovasi Teknologi Terapan, 2024)
Currently, using natural fibers as composite reinforcement is a new pattern in material technology. Natural fiber-reinforced composite materials have sustainable potential in the industrial field because the natural fibers used significantly impact the composite's mechanical properties. However, the chemical content of natural fibers can affect the mechanical properties of the composite. Therefore, chemical treatment of fibers that will be used as composite reinforcement must be done to produce mechanical properties such as optimal impact strength. This research aims to see the effect of treatment time on citronella fibers and the type of treatment solution on the resulting impact strength. The method used in this research is a 2k factorial design. In this study, the impact test used the ISO 179-01 standard reference with the treatment of citronella fiber soaked using liquid smoke solution and fiber boiling using turmeric solution, and the length of the treatment process was 1 hour and 3 hours. The results showed that the interaction between the type of solution and the length of treatment time affected the impact strength.